Education Enhanced by Information and Communication Technologies - SINGH, MR. KARAMJEET (The journal of contemporary issues in business and government, 2021)
In all facets of human life, knowledge and communication technology (ICTs) are becoming indissoluble entities. The utilization of ICT has profoundly modified the processes and methods of nearly any type of job, policy and public services. ICT have started to participate in education although it hasn't had as much impact as compared to other areas of activity. The transition from environment to new medias and information has increased the importance of Information and Communication Technologies in education and will continue to expand and to evolve in the 21st century. ICT is a vital aspect of the new environment. ICT is an integral feature. Society and culture in fact have to be adapted to the difficulties of era of knowledge. The standard and quantity of schooling in tertiary educational establishments has undeniably influenced ICT. There needs to be a clear emphasis on the numerous constraints on ICT usage as a higher education change agent, such that ICT continues to perform its high position in transforming tertiary institutions.